2021
DOI: 10.3390/su132413906
|View full text |Cite
|
Sign up to set email alerts
|

Hubs for Circularity: Geo-Based Industrial Clustering towards Urban Symbiosis in Europe

Abstract: Since the Green Deal, ambitious climate and resource neutrality goals have been set in Europe. Here, process industries hold a unique position due to their energy and material transformation capabilities. They are encouraged to develop cross-sectorial hubs for achieving not only climate ambition, but also joining a circular economy through urban–industrial symbiosis with both business and community stakeholders. This research proposes a data-based approach to identify potential hub locations by means of cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In urbanization economies, companies belong to different industries, which gives opportunities for firms to exchange their large variety of inputs and outputs. Similar ideas on the benefits of agglomeration have also been introduced in gray literature, under the concepts of "zero waste industrial hubs", "hubs for circularity" (Mendez Alva et al, 2021), and "circular city ports" (Architecture Workroom Brussels, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 3 more Smart Citations
“…In urbanization economies, companies belong to different industries, which gives opportunities for firms to exchange their large variety of inputs and outputs. Similar ideas on the benefits of agglomeration have also been introduced in gray literature, under the concepts of "zero waste industrial hubs", "hubs for circularity" (Mendez Alva et al, 2021), and "circular city ports" (Architecture Workroom Brussels, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…By studying the successes and failures of IS case studies, researchers identified the local environmental factors that facilitated resource exchanges, such as accessibility to nearby infrastructure, skilled labor, or by-products. Later studies addressed the issue of location more explicitly, by identifying the locations of industrial symbiosis clusters on a map, using surveys and interviews (Domenech et al, 2019), or using spatial statistical methods to analyze spatial data on industrial facilities (Mendez Alva et al, 2021).…”
Section: Circular Industrial Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, from the perspective of dynamic evolution, the cluster development of cities has become an important trend in urban development. From the objective results, the urban clusters formed by cluster development have become new economic growth poles, and this has led to the accelerated introduction of a series of urban cluster development plans [9][10][11]. At the same time, years of ultra-high speed and rough development have brought enormous pressure on resources and the environment, making China's green development increasingly important under the new normal [12,13].…”
Section: Introductionmentioning
confidence: 99%